Effect of zinc application strategies on maize grain yield and zinc concentration in mollisols - Martinez Cuesta, Nicolás; Carciochi, Walter; Sainz Rozas, Hernan Rene; Salvagiotti, Fernando; Colazo, Juan Cruz; Wyngaard, Nicolás; Eyherabide, Mercedes; Ferraris, Gustavo Nestor; Barbieri, Pablo (Taylor and Francis, 2021)
Maize (Zea mays L.) is highly susceptible to zinc (Zn) deficiency. Different application strategies (AS) can be utilized to improve grain yield (GY) and quality (Zn biofortification) by combining Zn fertilizer rate, source, timing, and placement techniques. This study aimed to evaluate whether different Zn-AS (soil, seed, and foliar) affect maize GY and grain Zn concentration in Mollisols with contrasting soil Zn availability and pH. Five site-years field experiments were carried out. Treatments (Zn-AS) were compared to a control, and included: seed-Zn, 0.3 kg Zn ha−1; foliar-Zn, 0.7 kg Zn ha−1 at V6 stage; and soil-Zn, 2.1 kg Zn ha−1 surface banded. Zinc fertilization increased GY (response ranged from 892 to 2519 kg ha−1) in four of five sites (p < 0.05). The evidence indicates that in scenarios of very low soil Zn availability (<0.9 mg kg−1 Zn-DTPA) greater Zn rates are required, and therefore soil-Zn and foliar-Zn are the more suitable AS. Grain Zn concentration ranged from 19.5 to 43.1 mg kg−1 and was not affected by Zn-AS. At all sites, even those showing GY response to Zn fertilization, grain Zn concentration in the control treatment was above the sufficiency threshold for maize GY (18 mg kg−1), indicating that this threshold needs to be updated for the current maize hybrids. Grain Zn concentration was predicted by the model: grain Zn concentration = 39.56 − 0.002 × GY + 9.62 × Zn-DTPA (R2 = 0.38).